Security Considerations in Multi-Cloud Environments with Seamless Integration: A Review of Best Practices and Emerging Threats - Thangaraju, Vigneshwaran (Transactions on Engineering and Computing Sciences, 2024)
Organizations in today's digital ecosystem that want to improve their operational efficiency, flexibility, and scalability must have multi-cloud environments. Combining several cloud servers has positive effects such as minimizing vendor lock-in, enhancing functional service quality, and meeting various customers’ demands. However, this entails numerous security perils such as, data leakage, cross-system operating ambiguities, and strong compliance demands. Hence, this paper focuses on the security issues associated with multi cloud models, and measures as the ZTA, higher encryption protocols, and Artificial Intelligence-based continuous monitoring. The place of compliance, specifically GDPR and CCPA, in protecting data sovereignty across areas is also underscored. In particular, the present work seeks to present aspects of secure and integrated multi-cloud, which will help organizations reduce risks, enhance compatibility and manage multi-cloud environments to address emerging business requirements. This study reviews emerging threats, identifies critical gaps, and proposes future directions for multi-cloud security frameworks.